2020
DOI: 10.1108/jiuc-09-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

A framework to improve university–industry collaboration

Abstract: PurposeThe purpose of this paper is to propose a framework to improve the effectiveness of university–industry collaboration (UIC). This work enhances the existing body of literature and knowledge regarding collaboration and offers concrete steps to be taken for effective collaboration between universities and industries.Research MethodologyA literature review to study the best practices, impediments to collaboration and the various models proposed in the past for successful UIC was conducted. A workshop and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 32 publications
3
80
0
2
Order By: Relevance
“…The successful academic leadership focuses on long-term strategic partnerships with a shared vision and strategy to achieve goals. The key individuals with an understanding of both academic and business worlds are the driving force behind successful partnerships (Awasthy et al, 2020;Kaloudis et al, 2019). When mutual understanding and ability to overcome the barriers are more potent than cultural and organisational differences, tensions, and conflicts, then expected outcomes are possible including mainly obtaining necessary resources and generating synergies of UCC (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The successful academic leadership focuses on long-term strategic partnerships with a shared vision and strategy to achieve goals. The key individuals with an understanding of both academic and business worlds are the driving force behind successful partnerships (Awasthy et al, 2020;Kaloudis et al, 2019). When mutual understanding and ability to overcome the barriers are more potent than cultural and organisational differences, tensions, and conflicts, then expected outcomes are possible including mainly obtaining necessary resources and generating synergies of UCC (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on an Audi and Technical University of Munich's case study, it was found that both partners had developed an efficient communication protocol, whereby they frequently met and communicated with each other in order to ensure a smooth and well-collaborated project (Edmondson et al, 2012). This finding was supported by Awasthy et al (2020), who advocated that both partners should utilise diverse communication platforms, such as face-to-face, and mobile and digital media communication to enhance their engagement in collaborative projects. They emphasized that the partners should meet and talk regularly to ensure a smooth collaboration process, as the progress of collaboration should also be communicated and monitored in each stage of collaboration.…”
Section: Factors Contributing Towards Successful University-industry Collaborative Projectmentioning
confidence: 87%
“…Besides, it can provide clear guidelines and acknowledge the stakeholders' responsibilities, thus enhancing understanding about their roles and responsibilities. These aspects about the importance of an IP policy has been supported by Awasthy et al (2020). They have emphasized that a clear IP policy would help reduce legal issues arising from conflicts in a collaboration.…”
Section: Factors Contributing Towards Successful University-industry Collaborative Projectmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the significant approach in empowering the sustainable development through strategic partnership engagement in determining an important instrument to adopt the positive feeling involved with optimistic mechanism progression to achieve the societal balance. Through the critical mechanism on considering the initiative of sustainability enhancement, the commitment on expanding the rise of partnerships in the setting of societal steering mechanisms could be initially incorporated with self-control management systems in enabling the accessibility of decision making policy to open recommendation for new progress initiative reform [93]. The variety of joining the cooperation along with the environmentally sustainable concern should be provided with the new arrangement assigned into the distinctive engagement process for strategic mechanisms in achieving the goal achievement.…”
Section: Implications For University and Industry's Strategic Partnershipmentioning
confidence: 99%